Arte e literatura infantil: a expressão visual em livros de imagem por Renato Moriconi e Rui de Oliveira - Alexânia de Avelar Campos (2023)
This dissertation is situated in the Education and Language research area, within the Federal University of Minas Gerais’ Graduate Program in Education. This work approaches the investigation of pictures in children’s literature, exploring how children’s literature and visual arts interweave to create wordless picture books. This literary genre consists of narratives built entirely with pictures. Understanding and analyzing such genres bears implications for both the field of Education, more generally, and readers’ education, more specifically. Its study must be handled in a singular manner due to its specific communication features and the production of a field of possible meanings. Therefore, illustrators not only have to create their readers’ memory and visual past, but, above all things, they also have to shape and educate one’s visual perception. The research’s main goal is to understand the points of proximity and the particularities among the wordless picture books of two illustrator-authors, Renato Moriconi and Rui de Oliveira. The theoretical framework upon which this investigation is based is supported by Belmiro (2008, 2011, 2014a, 2014b), Fittipaldi (2008), Lee (2012), Linden (2018), Oliveira (2008), Salisbury and Styles (2013) and Ramos (2011), who investigate illustrations in children’s books. Furthermore, the discussion is expanded with contributions from Bakhtin (2003, 2013), in the field of Philosophy of Language; Baudelaire (2006), Diderot (1993), and Venturi (2013), as representatives of Art criticism, taking into consideration that being in touch with a range of literary and artistic pieces bears implications for the process of human formation (Candido, 1999). The corpus for analysis in this investigation consisted of six pieces by Renato Moriconi and six pieces by Rui de Oliveira, focusing on each author’s aesthetic propositions (Christin, 2006), drawing on the following categories: color, ranging from black to white in its shades of grey; interpicturality; interlanguages; and human depiction. The methodology adopted in this research is based on a comparative approach for the study of literary pieces, assuming that Comparative Literature has a broader objective, seeking to advance understandings of issues in the literary field which require broad perspectives on our conceptions of wordless picture books (Carvalhal, 2006). By approaching the origins and influences that shaped the experiences of the authors encompassed by the research corpus, it is possible to understand the particularities and affinities among them, which are intrinsically connected to their intellectual, professional and aesthetic constitution. The results indicate how each of the authors establishes singular relationships with different languages in the process of making wordless picture books. Thus, wordless picture books are cultural artifacts that amplify our ways of talking about and seeing the world, and their exploration requires a specific approach due to their discursive features.